2012
DOI: 10.1007/s00247-012-2358-6
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of US for the diagnosis of pediatric acute appendicitis in a real-life setting: how can we improve the diagnostic value of sonography?

Abstract: In day-to-day use, US does not perform as purported in the literature. We do not visualize the appendix as often as we should and false-negative and false-positive exams are too common. To improve the diagnostic performance of this modality, involvement by experienced personnel and/or additional training is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
57
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 32 publications
7
57
1
2
Order By: Relevance
“…However the false negative rates for both groups (Table 1) were slightly higher or in line with other studies in the literature [12][13][14]. We also realize that the reported sensitivity in the literature is higher than that reported in our study, 67% versus 88% [15].…”
Section: Journal Of Pediatric Carei Issn 2471-805xcontrasting
confidence: 52%
See 1 more Smart Citation
“…However the false negative rates for both groups (Table 1) were slightly higher or in line with other studies in the literature [12][13][14]. We also realize that the reported sensitivity in the literature is higher than that reported in our study, 67% versus 88% [15].…”
Section: Journal Of Pediatric Carei Issn 2471-805xcontrasting
confidence: 52%
“…On the other hand, a study of 1,009 US evaluations in pediatric appendicitis found a higher detection rate of the appendix when the study was performed by specialized pediatric sonographers in comparison to general sonographers; however a conclusion of outcome with regard to appendicitis was not addressed [13]. The only patient specific factor that influenced visualization of the appendix reported was body habitus [13].…”
Section: Journal Of Pediatric Carei Issn 2471-805xmentioning
confidence: 99%
“…[1][2][3][4][5][6] Despite its advantages, 7 ultrasound (US) by itself has limited diagnostic utility for suspected appendicitis, 8 with the rate of equivocal examinations in some studies approaching 50%. [9][10][11][12] Several scoring systems, including the pediatric appendicitis score (PAS), 13 also do not perform well in isolation at diagnosing appendicitis. [14][15][16][17][18][19][20][21] An intravenous contrast-enhanced computed tomography (CT) scan is currently recommended in children with equivocal screening US results.…”
mentioning
confidence: 99%
“…While dedicated paediatric sonographers are more likely than their general counterparts to locate the appendix,32, 33 many children do not present to specialist paediatric departments. Definitive sonographic criteria or techniques that improve accuracy and assist diagnosis would be of particular benefit in these cases.…”
Section: Introductionmentioning
confidence: 99%